Sekolah Rumah Ramah Anak sebagai Solusi Pendidikan Jarak Jauh di Tengah Pandemi Covid-19 - Nuriana, Zulfa Ilma; Zahra, Alifarose Syahda (GERAM: Gerakan Aktif Menulis, 2020)
Covid-19 pandemic has a major impact on the world of education. Around 24.9% of students experience anxiety due to the Covid-19 Pandemic. Face-to-face education has also shifted to the Distance Education (PJJ) system. This shift is what worries parents because their children experience difficulties in self-regulation and understanding the material. Therefore, the researcher tried to provide a solution to this problem through this research. This research was qualitative. The method used was a literature study, interviews, and elementary school students' observations in Tulungagung and Blitar regencies. This study's results were that researchers recommend Child-Friendly Home Schools to the community, especially parents, because it was effectively applied in the learning process during the Covid-19 Pandemic.